Ulnar Artery Absence Together with the Median Artery - Okur, Mehmet İhsan; Yıldırım, Mustafa Alpagan; Bingöl, İsmet; Örter, Zübeyir; Alsancak, Ümit (Fırat University, 2007)
Upper extremities have often variations in arteriel system. Some of forearm vessels are regressed after embrionic stage. However, absence of ulnar artery is rarely seen. Normally, median artery exist in fetal period and it disappears after birth. In the present case, we performed an exploration for evaluating probable nerve damage after forearm wounding and observed the existence of median artery but absence of ulnar artery. Consequently, in the operation forearm, probable anatomic variations of vessels at related region should be taken it consideration. ©2007, Firat University, Medical Faculty

Üst ekstremitede arteriyel sistemin varyasyonları sıktır. Önkol arter sistemindeki damarlardan bazıları embriyonik dönemden sonra gerilemektedir. Ulnar arter yokluğu oldukça nadir gözlenen bir durumdur. Median arter normalde fetal dönemde bulunur ama doğumdan sonra gözlenmesi nadirdir. Olgumuzda sağ önkol yaralanması sonrası sinir hasarını görmek amacıyla yapılan eksplorasyonda median arter varlığı saptandıktan sonra birlikte ulnar arter yokluğu da gözlendi. Anatomik yapılarda olası değişiklikler ilgili vücut bölümlerinin damarlanmasına göre önkola yapılacak cerrahi girişimler için olası bu tür anatomik varyasyonlar göz önüne alınmalıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Ulnar Arter Yokluğu ile Birlikte Görülen Median Arter